Wear-resistant cam shaft and machining process thereof

By using alloy materials with specific chemical composition and multi-stage processing technology, a high-hardness composite coating and nitriding layer is formed, which solves the problem of performance degradation caused by fatigue wear of the camshaft, significantly improves wear resistance and corrosion resistance, and extends the Its service life and improves performance in high load environments.

CN119287275APending Publication Date: 2025-01-10ZHEJIANG BOXING IND & TRADE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411423416.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When the camshaft is running at high speed, fatigue wear caused by periodic impact loads, resulting in an increase in valve gap and affecting engine performance. It is difficult for the prior art to effectively improve its wear resistance.

Method used

Alloy materials with specific chemical compositions, including chromium, nickel, carbon, molybdenum, vanadium, high-silicon aluminum alloys, niobium and titanium, are made through precise design and multi-stage processing processes such as smelting, incubation treatment, solid solution treatment, laser cladding , plasma nitriding and phosphating treatment to form a high-hardness composite coating and nitriding layer, improving the material's wear resistance and corrosion resistance.

Benefits of technology

It significantly improves the wear resistance, toughness and fatigue resistance of the camshaft, extends its service life, ensures stability and reliability in high temperature and high impact environments, significantly reduces wear and friction, and improves surface hardness and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of metal material processing application, and discloses a wear-resistant camshaft and a processing technology thereof.The wear-resistant camshaft comprises, by mass, 10-12% of chromium, 5-7% of nickel, 3-4% of carbon, 2-3% of molybdenum, 0.5-1% of vanadium, 0.2-0.3% of a high-silicon aluminum alloy, 0.1-0.3% of niobium, 0.1-0.2% of titanium and the balance Fe and inevitable impurities. The machining process comprises the steps that S1, raw materials containing the chemical components are smelted, discharged and inoculated, a covering agent is added again, stirring and slagging-off are conducted, and an alloy melt is obtained; s2, casting the alloy melt into a camshaft blank; s3, the blank is subjected to solution treatment and aging treatment; s4, the treated blank is subjected to high-frequency quenching and rough machining, and a camshaft preformed part is obtained; s5, the preformed part is subjected to laser cladding treatment, and a composite coating is formed; s6, carrying out plasma nitriding treatment on the cladded camshaft; and S7, the nitrided camshaft is subjected to phosphating treatment, and the finished camshaft is obtained. The wear resistance of the camshaft can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material processing and application, and in particular to a wear-resistant camshaft and a processing technology thereof. Background Art

[0002] The camshaft is a key component in the engine. Its main body is a cylindrical rod with a length roughly the same as that of the cylinder block. Several cams are installed on it. These cams drive the valves by pushing the tappets or rocker arms, thereby controlling the opening and closing of the valves, and then regulating the inflow and outflow of fuel and air to achieve the normal working cycle of the engine. When the engine is running at high speed, the camshaft rotates at high speed, causing the working surface of the cam to bear periodic impact loads, which will cause fatigue wear. Once the wear exceeds a certain critical value, the valve clearance will increase, causing the valve opening time to be delayed and the degree of opening to be insufficient, which will seriously affect the performance of the engine.

[0003] In order to reduce this kind of wear, it is very important to improve the wear resistance of the camshaft. In theory, the wear rate is inversely proportional to the hardness of the worn surface, so increasing the hardness of the cam working surface is the key to improving its wear resistance. However, in actual production, it is often difficult to achieve the ideal wear resistance of the camshaft due to the unreasonable selection of casting material formula and the control of temperature and time during processing. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a wear-resistant camshaft and a processing technology thereof, which can improve the wear resistance of the camshaft.

[0005] The present invention solves the above technical problems by the following technical means:

[0006] In a first aspect, the present invention discloses a wear-resistant camshaft, whose chemical composition, measured by mass percentage, includes 10-12% chromium, 5-7% nickel, 3-4% carbon, 2-3% molybdenum, 0.5-1% vanadium, 0.2-0.3% high silicon aluminum alloy, 0.1-0.3% niobium, 0.1-0.2% titanium, and the balance is Fe and unavoidable impurities.

[0007] The alloy composition is precisely designed to optimize its wear resistance, strength, toughness and fatigue resistance. Chromium, carbon, molybdenum and vanadium significantly improve the hardness and wear resistance of the material by forming hard phases such as carbides; nickel and high-silicon aluminum alloys enhance the toughness, corrosion resistance and oxidation resistance of the material; the addition of niobium and titanium refines the grains and improves the fatigue resistance of the material. In addition, iron, as a matrix material, provides basic structural and toughness support, achieving an optimized combination of material properties as a whole.

[0008] In a second aspect, the present invention discloses a processing technology for a wear-resistant camshaft, the processing technology comprising the following steps: S1. smelting raw materials including chromium, nickel, carbon, molybdenum, vanadium, high silicon aluminum alloy, niobium, titanium and iron, taking them out of the furnace, inoculating them, adding a covering agent, stirring them, and slagging them to obtain an alloy melt;

[0009] S2. The alloy melt is cast into a camshaft blank;

[0010] S3. The blank is subjected to solution treatment and aging treatment;

[0011] S4. The processed blank is subjected to high-frequency quenching and rough machining to obtain a camshaft preform;

[0012] S5. The preform is subjected to laser cladding treatment to form a composite coating;

[0013] S6. Plasma nitriding treatment is performed on the camshaft after cladding;

[0014] S7. Perform phosphating treatment on the nitrided camshaft to obtain a finished camshaft.

[0015] First, the raw materials are smelted and inoculated to ensure uniform alloy composition, and the melt is further purified by adding a covering agent to eliminate impurities and obtain a high-quality alloy melt. After casting into a blank, the blank undergoes a solution treatment and an aging treatment to refine the internal grains of the material and stabilize the structure, laying the foundation for subsequent processing. High-frequency quenching and rough machining give the blank the required shape and basic mechanical properties. Laser cladding forms a high-hardness composite coating on the surface to enhance wear resistance. Plasma nitriding treatment further improves the surface hardness and wear resistance, while phosphating treatment improves the surface corrosion resistance, and finally produces a finished camshaft with excellent wear resistance.

[0016] Preferably, in terms of weight percentage, the inoculant used in the inoculation treatment in step S1 comprises 75-80 parts of ferrosilicon, 1-5 parts of ZnO-TiO2 composite material, 0.1-0.2 parts of strontium, and 0.5-1.5 parts of aluminum, and the amount of the inoculant accounts for 0.2-0.5% of the weight of the melt.

[0017] Ferrosilicon, as the main component, can effectively promote graphite nucleation and improve the graphitization ability of the melt, thereby improving the mechanical properties of the alloy. ZnO-TiO2 composite materials can improve the oxidation resistance and wear resistance of the material, strontium can refine the grains and enhance the toughness of the alloy, and aluminum helps to improve the fluidity and uniformity of the melt. The use of inoculants can ensure that the melt forms a uniform organizational structure during the cooling process, reduce casting defects, and improve the overall quality of the alloy.

[0018] Preferably, in terms of mass fractions, the covering agent in step S1 includes 30-35 parts of calcium oxide, 20-25 parts of silicon dioxide, 15-20 parts of calcium carbonate, 10-15 parts of sodium fluoride, 10-15 parts of aluminum oxide, 5-7 parts of carbon powder, and 3-5 parts of borax; the amount of the covering agent used is 0.5-1% of the weight of the melt.

[0019] Calcium carbonate decomposes to form calcium oxide at high temperature, which can effectively remove oxide impurities in the melt and play a purifying role. Silicon dioxide, as the main film-forming substance, works together with other ingredients to form a stable covering film to protect the melt from the intrusion of external oxygen and prevent oxidation. Sodium fluoride reduces the viscosity of the melt and improves the fluidity and spreadability of the covering agent on the surface of the melt. Alumina enhances the stability and chemical corrosion resistance of the covering film, and carbon powder further reduces the contact area between the melt and the air to prevent oxidation. Borax, as a flux, lowers the melting point and promotes the uniform distribution of the covering agent to ensure the covering effect.

[0020] Preferably, the solution treatment in step S3 is carried out at 1050-1150° C., and then rapid quenching is performed after keeping the temperature for 2-4 hours, followed by aging treatment at 400-500° C., and then air cooling after keeping the temperature for 6-8 hours.

[0021] Preferably, the high-frequency quenching in step S4 is performed at 800-900° C., and air cooling is performed after forging.

[0022] Preferably, during the laser cladding treatment in step S5, the alloy used contains 75-80% chromium carbide and 20-25% nickel-chromium alloy.

[0023] Preferably, the plasma nitriding treatment time of step S6 is 12-24 hours, the thickness of the nitriding layer is 0.3-0.5 mm, and the nitriding treatment temperature is 500-600°C.

[0024] Preferably, the phosphating treatment in step S7 adopts a high temperature phosphating process, which is carried out at 250-300° C., and the thickness of the phosphating film is 5-15 μm.

[0025] Beneficial effects of the present invention:

[0026] (1) The wear-resistant camshaft of the present invention exhibits excellent wear resistance and mechanical properties, especially under high temperature, high impact load and complex working conditions. The alloy material not only has extremely high wear resistance, but also has good toughness, fatigue resistance and corrosion resistance, which significantly extends the service life and reliability of the camshaft and ensures its stable performance in long-term high-intensity operation.

[0027] (2) The wear-resistant camshaft uses three-stage surface treatment measures to improve its wear resistance. First, the laser cladding treatment forms a composite coating with high hardness and excellent wear resistance on the surface of the camshaft, which effectively extends its service life. The plasma nitriding treatment forms a high-hardness and wear-resistant nitriding layer, which significantly enhances its wear resistance and fatigue life. In addition, the high-temperature phosphating process used in the phosphating treatment greatly improves the corrosion resistance and lubrication properties of the camshaft surface, reduces wear and friction, and effectively improves the long-term stability and reliability of the camshaft in harsh environments. The high wear resistance, excellent surface hardness, and good corrosion resistance of the camshaft ensure that the wear-resistant camshaft of the present invention has excellent performance in high-load and high-wear environments and significantly extends its service life. DETAILED DESCRIPTION

[0028] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention:

[0029] Example 1

[0030] The chemical composition ratio of this embodiment is 10% chromium, 5% nickel, 3% carbon, 2% molybdenum, 0.5% vanadium, 0.2% high silicon aluminum alloy, 0.1% niobium, 0.1% titanium, and the balance is Fe and unavoidable impurities.

[0031] S1. Smelting raw materials including chromium, nickel, carbon, molybdenum, vanadium, high silicon aluminum alloy, niobium, titanium and iron, taking out of the furnace, inoculating, adding a covering agent again, stirring, slagging, and obtaining an alloy melt;

[0032] The inoculant contains 75kg ferrosilicon, 1kg ZnO-TiO2 composite material, 0.1kg strontium, and 0.5kg aluminum, and the amount of the inoculant accounts for 0.2% of the melt weight.

[0033] The covering agent includes 30kg of calcium oxide, 20kg of silicon dioxide, 15kg of calcium carbonate, 10kg of sodium fluoride, 10kg of aluminum oxide, 5kg of carbon powder and 3kg of borax; the amount of covering agent used is 0.5% of the weight of the melt.

[0034] S2. The alloy melt is cast into a camshaft blank;

[0035] S3. The blank is subjected to solution treatment and aging treatment;

[0036] The solution treatment was carried out at 1050°C, followed by rapid quenching after 4 hours of holding, and then aging treatment was carried out at 400°C, followed by air cooling after 8 hours of holding.

[0037] S4. The processed blank is subjected to high-frequency quenching at 800°C, air cooling, and rough machining to obtain a camshaft preform;

[0038] S5. The preform is subjected to laser cladding treatment to form a composite coating;

[0039] During the laser cladding process, the alloy used contains 75% chromium carbide and 25% nickel-chromium alloy.

[0040] S6. Plasma nitriding treatment is performed on the camshaft after cladding;

[0041] The plasma nitriding treatment time is 12 hours, the nitriding layer thickness is 0.3 mm, and the nitriding treatment temperature is 500°C.

[0042] S7. The nitrided camshaft is subjected to phosphating treatment at 250° C., and the phosphating film thickness is 5 μm, thereby obtaining a finished camshaft.

[0043] Example 2

[0044] The chemical composition ratio of this embodiment is 11% chromium, 6% nickel, 3.5% carbon, 2.5% molybdenum, 0.75% vanadium, 0.25% high silicon aluminum alloy, 0.2% niobium, 0.15% titanium, and the balance is Fe and unavoidable impurities.

[0045] S1. Smelting raw materials including chromium, nickel, carbon, molybdenum, vanadium, high silicon aluminum alloy, niobium, titanium and iron, taking out of the furnace, inoculating, adding a covering agent again, stirring, slagging, and obtaining an alloy melt;

[0046] The inoculant contains 77.5kg ferrosilicon, 3kg ZnO-TiO2 composite material, 0.15kg strontium, and 1kg aluminum. The amount of the inoculant accounts for 0.35% of the melt weight.

[0047] The covering agent includes 32.5kg of calcium oxide, 22.5kg of silicon dioxide, 17.5kg of calcium carbonate, 12.5kg of sodium fluoride, 12.5kg of aluminum oxide, 6kg of carbon powder and 4kg of borax; the amount of covering agent used is 0.75% of the weight of the melt.

[0048] S2. The alloy melt is cast into a camshaft blank;

[0049] S3. The blank is subjected to solution treatment and aging treatment;

[0050] The solution treatment was carried out at 1100°C, followed by rapid quenching after 3 hours of holding, and then aging treatment was carried out at 450°C, followed by air cooling after 7 hours of holding.

[0051] S4. The processed blank is subjected to high-frequency quenching at 850°C, air cooling, and rough machining to obtain a camshaft preform;

[0052] S5. The preform is subjected to laser cladding treatment to form a composite coating;

[0053] During the laser cladding process, the alloy used contains 77.5% chromium carbide and 22.5% nickel-chromium alloy.

[0054] S6. Plasma nitriding treatment is performed on the camshaft after cladding;

[0055] The plasma nitriding treatment time is 18 hours, the nitriding layer thickness is 0.4 mm, and the nitriding treatment temperature is 550°C.

[0056] S7. The nitrided camshaft is subjected to phosphating treatment at 275° C., and the phosphating film thickness is 10 μm, thereby obtaining a finished camshaft.

[0057] Example 3

[0058] The chemical composition ratio of this embodiment is 12% chromium, 7% nickel, 4% carbon, 3% molybdenum, 1% vanadium, 0.3% high silicon aluminum alloy, 0.3% niobium, 0.2% titanium, and the balance is Fe and unavoidable impurities.

[0059] S1. Smelting raw materials including chromium, nickel, carbon, molybdenum, vanadium, high silicon aluminum alloy, niobium, titanium and iron, taking out of the furnace, inoculating, adding a covering agent again, stirring, slagging, and obtaining an alloy melt;

[0060] The inoculant contains 80kg ferrosilicon, 5kg ZnO-TiO2 composite material, 0.2kg strontium, and 1.5kg aluminum. The amount of the inoculant accounts for 0.5% of the melt weight.

[0061] The covering agent includes 35kg of calcium oxide, 25kg of silicon dioxide, 20kg of calcium carbonate, 15kg of sodium fluoride, 15kg of aluminum oxide, 7kg of carbon powder and 5kg of borax; the amount of covering agent used is 1% of the weight of the melt.

[0062] S2. The alloy melt is cast into a camshaft blank;

[0063] S3. The blank is subjected to solution treatment and aging treatment;

[0064] The solution treatment was carried out at 1150°C, followed by rapid quenching after 2 hours of holding, and then aging treatment was carried out at 500°C, followed by air cooling after 6 hours of holding.

[0065] S4. The processed blank is subjected to high-frequency quenching at 900°C, air cooling, and rough machining to obtain a camshaft preform;

[0066] S5. The preform is subjected to laser cladding treatment to form a composite coating;

[0067] During the laser cladding process, the alloy used contains 80% chromium carbide and 20% nickel-chromium alloy.

[0068] S6. Plasma nitriding treatment is performed on the camshaft after cladding;

[0069] The plasma nitriding treatment time is 24 hours, the nitriding layer thickness is 0.5 mm, and the nitriding treatment temperature is 600 °C.

[0070] S7. The nitrided camshaft is phosphated at 300°C, and the phosphating film thickness is 15 μm, thereby obtaining a finished camshaft.

[0071] Comparative Example 1

[0072] The difference between this embodiment and embodiment 2 is that the use of the inoculant and the covering agent in step S1 is omitted.

[0073] Comparative Example 2

[0074] The difference between this embodiment and embodiment 2 is that the surface treatment in steps S5 to S7 is omitted.

[0075] Performance test conditions:

[0076] Load: 1000 N

[0077] Friction speed: 200 rpm

[0078] Temperature: Normal temperature 25℃

[0079] Test time: The samples of each embodiment were subjected to friction and wear test for 10 hours.

[0080] The performance test results are shown in Table 1

[0081]

[0082] The camshaft of Example 2 has significantly improved wear resistance through inoculants, covering agents and surface treatment processes. Compared with Comparative Examples 1 and 2, Example 2 not only shows obvious advantages in friction coefficient, wear rate and surface hardness, but also has less surface wear, and is suitable for use in working environments with high wear resistance requirements.

[0083] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A wear-resistant camshaft, characterized in that: Calculated in mass percentage, its chemical composition includes 10-12% chromium, 5-7% nickel, 3-4% carbon, 2-3% molybdenum, 0.5-1% vanadium, 0.2-0.3% high silicon aluminum alloy, 0.1-0.3% niobium, 0.1-0.2% titanium, and the balance is Fe and unavoidable impurities.

2. A processing technology for a wear-resistant camshaft as claimed in claim 1, characterized in that: The processing technology comprises the following steps: S1. The raw materials including chromium, nickel, carbon, molybdenum, vanadium, high silicon aluminum alloy, niobium, titanium and iron are smelted, taken out of the furnace, inoculated, and then a covering agent is added, and stirred and slag is removed to obtain an alloy melt; S2. The alloy melt is cast into a camshaft blank; S3. The blank is subjected to solution treatment and aging treatment; S4. The processed blank is subjected to high-frequency quenching and rough machining to obtain a camshaft preform; S5. The preform is subjected to laser cladding treatment to form a composite coating; S6. Plasma nitriding treatment is performed on the camshaft after cladding; S7. Perform phosphating treatment on the nitrided camshaft to obtain a finished camshaft.

3. The processing technology of a wear-resistant camshaft according to claim 2 is characterized in that: In terms of weight percentage, the inoculant used in the inoculation treatment in step S1 comprises 75-80 parts of ferrosilicon, 1-5 parts of ZnO-TiO2 composite material, 0.1-0.2 parts of strontium, and 0.5-1.5 parts of aluminum, and the amount of the inoculant accounts for 0.2-0.5% of the weight of the melt.

4. The processing technology of a wear-resistant camshaft according to claim 2, characterized in that: In terms of weight percentage, the covering agent in step S1 includes 30-35 parts of calcium oxide, 20-25 parts of silicon dioxide, 15-20 parts of calcium carbonate, 10-15 parts of sodium fluoride, 10-15 parts of aluminum oxide, 5-7 parts of carbon powder, and 3-5 parts of borax; the amount of the covering agent used is 0.5-1% of the weight of the melt.

5. The processing technology of a wear-resistant camshaft according to claim 2, characterized in that: The solution treatment in step S3 is carried out at 1050-1150° C., followed by rapid quenching after 2-4 hours of heat preservation, and then aging treatment is carried out at 400-500° C., followed by air cooling after 6-8 hours of heat preservation.

6. The processing technology of a wear-resistant camshaft according to claim 2, characterized in that: The high-frequency quenching in step S4 is performed at 800-900° C., and air cooling is performed after forging.

7. The processing technology of a wear-resistant camshaft according to claim 2, characterized in that: During the laser cladding process in step S5, the alloy used contains 75-80% chromium carbide and 20-25% nickel-chromium alloy.

8. The processing technology of a wear-resistant camshaft according to claim 2, characterized in that: The plasma nitriding treatment time of step S6 is 12-24 hours, the thickness of the nitriding layer is 0.3-0.5 mm, and the nitriding treatment temperature is 500-600°C.

9. The processing technology of a wear-resistant camshaft according to claim 2, characterized in that: The phosphating treatment in step S7 adopts a high temperature phosphating process and is carried out at 250-300° C. The thickness of the phosphating film is 5-15 μm.